A comparative judgment approach to assessing Chinese Sign Language interpreting. (April 2022) - Han, Chao; Xiao, Xiaoyan
The quality of sign language interpreting (SLI) is a gripping construct among practitioners, educators and researchers, calling for reliable and valid assessment. There has been a diverse array of methods in the extant literature to measure SLI quality, ranging from traditional error analysis to recent rubric scoring. In this study, we want to expand the terrain of SLI assessment, by exploring and evaluating a novel method, known as comparative judgment (CJ), to assess SLI quality. Briefly, CJ involves judges to compare two like objects/items and make a decision by choosing the one with higher quality. The binary outcomes from repeated comparisons by a group of judges are then modelled statistically to produce standardized estimates of perceived quality for each object/item. We recruited 12 expert judges to operationalize CJ via a computerized system to assess the quality of Chinese Sign Language interpreting produced by 36 trainee interpreters. Overall, our analysis of quantitative and qualitative data provided preliminary evidential support for the validity and utility of CJ in SLI assessment. We discussed these results in relation to previous SLI literature, and suggested future research to cast light on CJ's usefulness in applied assessment contexts.